The Primary Complete Mitochondrial Genome of the Lappet Moth Brahmophthalma hearseyi (Lepidoptera: Brahmaeidae) and Related Phylogenetic Analysis - Shan Yang; Shangren Gao; Shiyu Cai; Zhiwen Zou; Tianrong Xin; Bin Xia (Insects, 2021)
Background: Brahmophthalma hearseyi (Lepidoptera: Brahmaeidae) is widely distributed across China. Its larvae damage the leaves of many plants such as those belonging to the Oleaceae family, causing significant economic losses and seriously affecting the survival and reproduction of Cervus nippon; however, genetic data for this species are scarce. Methods: The complete mitochondrial genome (mitogenome) of B. hearseyi was sequenced using long-PCR and primer-walking methods. Phylogenetic analysis that was based on 13 PCGs and two rRNAs was carried out using the neighbor-joining and Bayesian interference methods. Results: The mitogenome is a typical circular molecule that is made up of 15,442 bp, which includes 13 protein-coding genes (PCGs), 2 ribosomal RNA (rRNA) genes, 22 transfer RNA (tRNA) genes, and an A + T-rich region (456 bp). All of the PCGs, except for COX1 and COX2, start with ATN codons. COX2 and ND5 use the incomplete termination codon T, and 11 other PCGs use the typical stop codon TAA. All tRNA genes, except for trnS1 and trnS2, display a typical cloverleaf structure; trnS1 lacks the “DHU” arm, whereas trnS2 exhibits two mismatched base pairs in the anticodon stem. Phylogenetic analysis showed that B. hearseyi is clustered into Brahmaeidae, and the phylogenetic relationships are (Brahmaeidae + Lasiocampidae) + (Bombycidae + (Sphingidae + Saturniidae)). Conclusions: This study provides the first mitogenomic resources for the Brahmaeidae.